Problem sprawiedliwości Bożej w świetle Listu do Rzymian - Kowalski, Marcin (Verbum Vitae, 2014)
In the present article, the author indicates the theme of God’s justice as a unifying thread of the Letter to the Romans. The analysis of the issue starts from a general overview of the idea of justice in the Greco-Roman culture, in the Old and New Testament. Next, the author presents the overall structure of the Letter to the Romans supplied with the distribution of the vocabulary of justice. The core of the article is the analysis of the differentiated argumentative parts of the letter (Rom 1–4; 5–8; 9–11) with the special attention paid to the issue of God’s justice. Paul presents it as the power of God that saves the humanity from the incoming judgment (Rom 1–4), as the giver of new life in the Spirit and freedom for the believers (Rom 5–8), and as the creative will of God that will not cease until it brings everybody, including Israel, to salvation (Rom 9–11). At every stage of his argument, the apostle stresses that throughout the whole history of mankind God’s justice remained faithful to its original plan of salvation revealed and disclosed in the Old Testament.